Cobalt sulfide counter electrodes enhanced by a hydro-thermal treatment for use in platinum-free dye-sensitized solar cells. (August 2015) - Xiao, Yaoming; Han, Gaoyi; Chang, Yunzhen; Zhang, Ying; Lin, Jeng-Yu
Graphical abstract: NaHS hydro-thermal treatment is employed to improve the electrocatalytic activity and long-term stability of the CoS CE. The DSSC with the treated CoS CE obtains an enhanced photovoltaic conversion efficiency of 7.16%, which increases by 28.09% than that using untreated CoS CE (5.59%). Highlights: NaHS treatment is employed to enhance the stability of CoS counter electrode (CE). Nanoflake arrays CoS CE based on the NaHS treatment shows high catalytic activity. The efficiency of the DSSC with the treated CoS CE reaches 7.16%. Abstract: A small quantity of uncontrollable cobalt (Co) and cobalt hydroxide (Co(OH)2 ), remaining in the cobalt sulfide (CoS) film prepared by the cyclic voltammetry (CV) electrodeposition method, will negatively influence the catalytic activity and stability of the CoS counter electrode (CE). The residual Co and Co(OH)2 compounds are dissolved after a sodium hydrosulfide (NaHS) hydro-thermal treatment. CV, electrochemical impedance spectroscopy (EIS), and Tafel polarization curves indicate that the treated CoS CE exhibits superior electrocatalytic activity and stability for the I3 − reduction. The platinum-free dye-sensitized solar cell (DSSC) using the treated CoS CE obtains an enhanced photovoltaic conversion efficiency of 7.16% compared to that using the untreated CoS CE (5.59%) under full sunlight illumination (100 mW cm −2, AM1.5 G).